Investigation of the Intercultural Sensitivities of the Students of the Faculty of Health Sciences - Çınar, Fadime (Ömer Fettahoğlu, 2020)
Objective: Turkey has a multicultural social structure. The relationship between culture and care services needs to be understood to serve the population of different cultural characteristics and provide safe and effective care.In this context, the study aims to determine the intercultural sensitivity and related factors of the students studying in the faculty of health sciences, which will be future health professionals. Materials and Methods: The populatıon of this descriptive study consisted of 732 students from Nutrition and Dietetics, Social Work, Nursing, and Health Management. They were educated in the faculty of health sciences of a foundation university operating on the European side of Istanbul. In the research, it was aimed to reach the whole universe by not choosing the sample. Students who agreed to participate in the study were included in the study. However, 509 students who did not accept to participate in the research and did not attend school on the days when the data were collected were not included in the sample of the study and 223 students formed the sample. The data of the survey were collected between the dates of April 01-30, 2019, by survey method."Introductory Information Form" Intercultural Sensitivity Scale, which was created by the researchers in line with the literature, was used as a data collection tool.SPPS 25.0 statistical package program was used to evaluate the data. Continuous variables were expressed as mean ± standard deviation, categorical variables as numbers or percentages. Kolmogorov-Smirnov test was used to assess whether the distribution of variables is normal. It was determined that the variables showed normal distribution. Variables with normal distribution in statistical comparisons; It was evaluated using two independent sample tests and One Way ANOVA tests for more than two variables, p <0.05 was considered statistically significant. Results: The average age of 223 students included in the study is 21.73 ± 1.85, 98.72% of them are in the 20-24 age group, and 82.5% are women. 32.7% of the students (n = 73) Health Management, 24.2% Social Work (n = 54), 16.1% (n = 36) Nursing, 27% Nutrition and Dietetics ( n = 60) department student. The total score that the students got from the Intercultural Sensitivity Scale is 79.63 ± 11.07, and it is at the intermediate level. When the relationship between factors affecting intercultural sensitivity and scale total score is examined; The intercultural sensitivity level was found to be significantly different in female students, nursing program students (p <0.05), and senior students according to their department variable. Conclusion: It was determined that the awareness of the importance of different intercultural sensitivity and importance of the students of the faculty of health sciences, who will be the future health professionals, is at a medium level.It is considered important to include intercultural education programs such as emotional-cognitive-behavioral education, self-awareness education, and cultural awareness education, which will help students acquire cultural awareness and awareness skills. Anahtar Kelimeler: Culture, Intercultural sensitivity, Health sciences students.

Amaç: Türkiye çok kültürlü bir toplumsal yapıya sahiptir. Farklı kültürel özelliklerdeki nüfusa hizmet etmek, güvenli ve etkili bakım sunmak için, kültür ve bakım hizmetleri arasındaki ilişkinin anlaşılması gereklidir. Bu kapsamda çalışmanın amacı, geleceğin birer sağlık profesyoneli olacak olan sağlık bilimleri fakültesinde öğrenim gören öğrencilerin kültürlerarası duyarlılıklarının ve ilişkili faktörlerin belirlenmesidir. Gereç ve Yöntem: Tanımlayıcı tipte olan bu araştırmanın evrenini İstanbul ilinde Avrupa yakasında faaliyette bulunan bir vakıf üniversitesinin sağlık bilimleri fakültesinde eğitim gören Beslenme ve Diyetetik. Sosyal Hizmet, Hemşirelik ve Sağlık Yönetiminden toplam 732 öğrenci oluşturdu. Araştırmada örneklem seçimine gidilmeyip, evrenin tamamına ulaşılması hedeflendi. Araştırmaya katılmayı kabul eden öğrenciler araştırma kapsamına alındı. Ancak çalışmaya katılmayı kabul etmeyen ve verilerin toplandığı günlerde okula devam etmeyen 509 öğrenci araştırmanın örneklemi kapsamına alınamadı ve örneklemi 223 öğrenci oluşturdu. Aştırmanın verileri 01-30 Nisan 2019 tarihleri arasında anket yöntemi ile toplandı. Veri toplama aracı olarak, araştırmacılar tarafından literatür doğrultusunda oluşturulan, "Tanıtıcı Bilgi Formu" Kültürlerarası Duyarlılık Ölçeği (KDÖ) kullanıldı. Verilerin değerlendirilmesinde SPPS 25.0 istatistik paket programı kullanıldı. Sürekli değişkenler ortalama±standart sapma, kategorik değişkenler sayı veya yüzde ile gösterildi. Değişkenlerin dağılımının normal olup olmadığını değerlendirmek için Kolmogorov - Smirnov testi kullanıldı. Değişkenlerin normal dağılım gösterdiği belirlendi. İstatistiksel karşılaştırmalarda normal dağılım gösteren değişkenler; Bağımsız iki örneklem testi ve ikiden fazla değişkenler için One Way ANOVA testleri kullanılarak değerlendirildi, p<0,05 istatistiksel olarak anlamlı kabul edildi. Bulgular: Çalışmaya dahil olan 223 öğrencinin yaş ortalaması 21,73±1,85 olup %98,72si 20-24 yaş grubu aralığındadır ve %82,5'i kadındır. Öğrencilerin %32,7' sı (n=73) Sağlık Yönetimi, %24,2'si Sosyal Hizmet (n=54), %16,1'i (n=36) Hemşirelik, %27'si Beslenme ve Diyetetik (n=60) bölümü öğrencisidir. Öğrencilerin Kültürlerarası Duyarlılık Ölçeğinden aldıkları toplam puan 79,63±11.07 olup, orta düzeydedir. Tıbbi hata tutumunu etkileyen faktörler ile ölçek toplam puanı arasındaki ilişki incelendiğinde; Öğrencilerin bulundukları bölüm değişkenine göre hemşirelik programı öğrencilerinde (p<0,05), başka kültürlerle etkileşimde bulunanlarda (p=0,001), yabancı dil bilenlerde (p=0,001) ve diğer kültürle etkileşimi olumlu olarak algılayanlarda (p=0,002) kültürlerarası duyarlılık düzeyi anlamlı olarak farklı bulundu. Sonuç: Geleceğin sağlık profesyonelleri olacak sağlık bilimleri fakültesi öğrencilerinin farklı kültürlerarası duyarlılığı ve öneminin farkındalığının orta düzeyde olduğu saptandı. Öğrencilerin eğitiminde kültürel duyarlılık ve farkındalık yeteneklerini elde etmelerine yardım edecek duygusal-bilişsel-davranışsal eğitim, öz-farkındalık eğitimi ve kültürel farkındalık eğitimi gibi kültürlerarası eğitim programlarının yer almasının önemli olduğunu düşünülmektedir
Keywords: Culture; Intercultural sensitivity; Health sciences students; Kültürlerarası duyarlılık; Tutum; Sağlık bilimleri fakültesi öğrencileri